The synaptic vesicle cycle: exocytosis and endocytosis in Drosophila and C. elegans. - Richmond, J.E.; Broadie, K.S. (Current Opinion in Neurobiology, 2002)
Advances in the study of Drosophila melanogaster and Caenorhabditis elegans have provided key insights into the processes of neurotransmission and neuromodulation. Work in the past year has revealed that Unc-13 and Rab3a-interacting molecule regulate the conformational state of syntaxin to prime synaptic vesicle fusion. Analyses of synaptotagmin support its role as a putative calcium sensor triggering vesicular fusion and highlight the possible role of SNARE complex oligomerization in the fusion mechanism. Characterization of endophilin mutants demonstrates that kiss-and-run endocytosis is a major component of synaptic vesicle recycling. In neuromodulation, dcaps mutants provide the first genetic insight into possible roles of the CAPS protein in mediating dense core vesicle fusion and modulating synaptic vesicle fusion.